2009
DOI: 10.1002/hipo.20545
|View full text |Cite
|
Sign up to set email alerts
|

Physical exercise leads to rapid adaptations in hippocampal vasculature: Temporal dynamics and relationship to cell proliferation and neurogenesis

Abstract: Increased levels of angiogenesis and neurogenesis possibly mediate the beneficial effects of physical activity on hippocampal plasticity. This study was designed to investigate the temporal dynamics of exercise-induced changes in hippocampal angiogenesis and cell proliferation. Mice were housed with a running wheel for 1, 3, or 10 days. Analysis of glucose transporter Glut1-positive vessel density showed a significant increase after 3 days of wheel running. Cell proliferation in the dentate gyrus showed a tren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
127
1
2

Year Published

2010
2010
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 190 publications
(135 citation statements)
references
References 70 publications
2
127
1
2
Order By: Relevance
“…Studies of physical exercise have shown that increases in neurogenesis with running (92) are coupled to increases in angiogenesis (93), and these factors are associated with an increase in cognitive function (94). Angiogenesis occurs alongside neurogenesis in embryonic development when the BBB is formed, but the BBB does not fully mature until 3 weeks postnatally, when cues from the neuroepithelium are thought to drive the wrapping of vessels by astrocytes (95).…”
Section: Discussionmentioning
confidence: 99%
“…Studies of physical exercise have shown that increases in neurogenesis with running (92) are coupled to increases in angiogenesis (93), and these factors are associated with an increase in cognitive function (94). Angiogenesis occurs alongside neurogenesis in embryonic development when the BBB is formed, but the BBB does not fully mature until 3 weeks postnatally, when cues from the neuroepithelium are thought to drive the wrapping of vessels by astrocytes (95).…”
Section: Discussionmentioning
confidence: 99%
“…This is in agreement with other studies that have reported cellular proliferation in the dentate gyrus of rats with exercise that is both forced and of short duration (less than three weeks [43,44]). Cell proliferation has been shown to increase after as little as three days of voluntary exercise in mice, becoming statistically significant only after 10 days [45]. However, there is some evidence that the stages of neurogenesis occur at a different rate in rats than in mice [46].…”
Section: Discussionmentioning
confidence: 99%
“…The process of angiogenesis is believed to contribute to hippocampal neurogenesis to some degree; indeed the Gage laboratory observed dense clusters of proliferating cells in close association with the vasculature (Palmer et al, 2000). Treadmill exercise and voluntary wheel running have been reported to increase blood vessel density, numbers of glucose transporter (Glut-1) + blood vessels and cerebral blood volume in animal models (Black et al, 1990;Pereira et al, 2007;Van der Borght et al, 2009). It is noteworthy that Pereira et al (2007) correlated the exercise-induced increases in DG cerebral blood volume with postmortem measurements of cell survival.…”
Section: Adult Hippocampal Neurogenesis and Exercisementioning
confidence: 99%